PENINGKATAN MINAT BELAJAR SISWA MELALUI METODE NUMBERED HEAD TOGETHER (NHT) PADA MATERI ASMAUL HUSNA DI KELAS IV SD NEGERI 056597 KP.PADANG KEC. SELESAI KAB.LANGKAT - Lely Ramadhan (Journal of Community Devation, 2025)
This study aims to improve the learning interest of fourth grade students of SD Negeri 056597 Kp.Padang on the material of Asmaul Husna through the Numbered Head Together Method. The research method used is Classroom Action Research (CAR) which is carried out in two cycles. The design of the research that will be used is the design developed by Kemmis and Mc Taggart which consists of four components, namely planning (plan), action (act), observation (observation), and reflection (reflection). The design in this study will be sought and examined, how efforts are made to improve students' learning interest in learning achievement in the PAI on the material of Asmaul Husna in grade IV using the Numbered Head Together (NHT) Method. The data analysis technique used in this study is the Numbered Head Together method because it allows students to become independent learners in cooperative learning, the information found, understood and evaluated by students becomes their own understanding. Students develop critical thinking skills as a result of the learning process. The results of the study showed that the NHT method was able to increase students' interest in learning the Asmaul Husna material, increasing students' interest in learning after using the NHT method also achieved good results.